2007
DOI: 10.1073/pnas.0704285104
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of imprinting and nuclear architecture in cycling cells

Abstract: (14) provided a first case-in-point. They performed FISH experiments in normal, phytohemagglutinin (PHA)-stimulated human lymphocytes with a probe covering a segment of the Angelman syndrome/Prader-Willi syndrome (AS/PWS) locus on HSA 15q11-13 and measured 3D interdistances between the two signals in samples of 50 nuclei at different interphase stages. Approximately 38% of nuclei at G 1 , Ϸ18% at early S phase, Ϸ58% at late S phase, and Ϸ18% at G 2 revealed distances Յ2 m, which were considered as a proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…The authors argued that transient "kissing" between the two loci is required for maintaining opposite imprints in cycling cells. This specific case of "kissing," however, could not be confirmed in a later study (Teller et al 2007).…”
Section: Dynamics and Interactions Of Specific Gene Loci Located On Tmentioning
confidence: 80%
“…The authors argued that transient "kissing" between the two loci is required for maintaining opposite imprints in cycling cells. This specific case of "kissing," however, could not be confirmed in a later study (Teller et al 2007).…”
Section: Dynamics and Interactions Of Specific Gene Loci Located On Tmentioning
confidence: 80%
“…Homologous associations were also shown to occur at the Beckwith-Wiedemann syndrome locus (BWS) of human chromosome 11p15, which contains which contains imprinted insulin-like growth factor 2 (IGF2) and H19 (a non-coding RNA) genes, suggesting that these associations might represent a general mechanism for regulating imprinting 41 . However, when, Teller et al revisited these findings they found no evidence for an increase of the fraction of nuclei with paired, oppositely imprinted AS/PWS or BWS loci at late S phase 43 . However, in agreement with the findings of LaSalle et al they did observe a significant homologous association between the centromeres of chromosome 11 (approximately 4 megabases away from the AS/PWS locus) during late S phase.…”
Section: Imprintingmentioning
confidence: 99%
“…However, in agreement with the findings of LaSalle et al they did observe a significant homologous association between the centromeres of chromosome 11 (approximately 4 megabases away from the AS/PWS locus) during late S phase. Teller et al predicted that this is mediated by a nucleolar organizer region (NOR) (which are known to undergo paring events) linked to the centromere of chromosome 15 (and by default the AS/PWS region) 43 . Indeed analysis of lymphoblastoid cells from Gorilla gorilla, in which the AS/PWS region is not linked to a NOR they actually observed increased distances between AS/PWS loci during late S phase 43 .…”
Section: Imprintingmentioning
confidence: 99%
“…An opposite example is the recent study of Angelman syndrome/PraderYWilli syndrome (AS/ PWS) loci by Teller et al (2007). Transient clustering of these loci at the late S-phase has earlier been suggested as a possible mechanism for maintenance of opposite imprinting, while Teller and co-authors argued against kissing of AS/PWS loci.…”
Section: Comparison Between Cells (Independent Samples)mentioning
confidence: 99%
“…For example, this approach helped to demonstrate that NORs (nucleolar organizers) of all NOR-bearing chromosomes tend to cluster (Teller et al 2007). NORs actually cluster around the nucleolus, and the discussed approach compensated for the variation in the position of the nucleolus.…”
Section: Reference Determined By the Studied Signalsmentioning
confidence: 99%